2022
DOI: 10.3390/antiox11061196
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction for Prediabetes and Type 2 Diabetes Using the Genetic Risk Score and Oxidative Stress Score

Abstract: We aimed to use a genetic risk score (GRS) constructed with prediabetes and type 2 diabetes-related single nucleotide polymorphisms (SNPs) and an oxidative stress score (OSS) to construct an early-prediction model for prediabetes and type 2 diabetes (T2DM) incidence in a Korean population. The study population included 549 prediabetes and T2DM patients and 1036 normal subjects. The GRS was constructed using six prediabetes and T2DM-related SNPs, and the OSS was composed of three recognized oxidative stress bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…MOTSc, and GSH/GSSG as well as IL-1β were significant for the transition from control to preDM, agreeing with previous research 77 . For the transition from preDM to T2DM GSH/GSSG, MOTSc, and 8-isoprostane were significant and highlighting the importance of mitochondrial involvement 78 . When the control group was compared to the T2DM group, IL-6 appeared in the model as an inflammatory marker 79 in addition to.…”
Section: Discussionmentioning
confidence: 93%
“…MOTSc, and GSH/GSSG as well as IL-1β were significant for the transition from control to preDM, agreeing with previous research 77 . For the transition from preDM to T2DM GSH/GSSG, MOTSc, and 8-isoprostane were significant and highlighting the importance of mitochondrial involvement 78 . When the control group was compared to the T2DM group, IL-6 appeared in the model as an inflammatory marker 79 in addition to.…”
Section: Discussionmentioning
confidence: 93%
“…Prediabetes, de ned based on glycemic parameters above NGT but below the diabetes threshold, is a high-risk condition for diabetes with an annualized conversion rate of 5-10% 22 . Previous studies have shown that T2DM PRS is associated with prediabetes 23,24 . However, no study showed that T2DM PRS predicts the progression from prediabetes to T2DM.…”
Section: Discussionmentioning
confidence: 96%